Evaluation of neutralizing antibody titers against SARS-CoV-2 JN.1 omicron subvariant during pregnancy - A case series study - Marie Didembourg; Clara David; Laure Morimont; Eva Cransquint; Julien Favresse; Jonathan Douxfils; Constant Gillot (Heliyon)
Background: SARS-CoV-2 infection during pregnancy poses health risks to both mother and fetus. This study investigates neutralizing antibodies (NAbs) against the SARS-CoV-2 JN.1 Omicron subvariant in pregnant women, focusing on responses to natural infection, vaccination, and passive immunity. Methods: A single-center, prospective study collected blood samples from 19 pregnant women at various pregnancy stages and postpartum. NAb titers were analyzed using a pseudovirus neutralization assay, with statistical analyses (p-value <0.05) conducted using unpaired t-test with Welch's correction. Results: Among participants, 63.2 % had at least one positive NAb titer, with only one vaccinated case. No significant difference in NAb titers was found between symptomatic and asymptomatic women. NAbs were detected in cord blood, especially when infection or vaccination occurred close to delivery, indicating passive immunity transfer to the newborn. Conclusion: NAb titers change dynamically during pregnancy, increasing then decreasing. Most pregnant women were asymptomatic and NAbs were effectively transferred to the fetus when infection or vaccination occurred near delivery. These findings highlight the importance of vaccination timing, suggesting late second or third trimester vaccination may provide better protection, emphasizing the need for adherence to vaccination guidelines to optimize maternal and neonatal immunity.